Solaris (Stanisław Lem) y Aelita (A.N. Tolstoi): el amor dentro del género de la ciencia ficción - Velis Blinova, Mabel Greta (Eslavística Complutense, 2007)
The article presents a comparative analysis of two great works (Solaris and Aelita) in order to show that both occupy a unique place in Science Fiction. The great Polish Science Fiction writer and the heterogeneous Russian Classic emphasize the man’s inner world and his emotions framing the genre in a universal feeling as it is the love.